PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA WARUNK UPNORMAL SEMARANG - Kristianti, Tina; Rivai, Alimuddin Rizzal (Jurnal Ilmiah Telaah Manajemen, 2018)
This study aims to examine and analyze the effect of price perceptin, prouct quality and service quality on customer satisfaction at warunk upnormal Semarang. The research location was at warunk upnormal Semarang, with a sample of 100 respondents. The analysis tool used is multiple regression, as for testing the hypothesis using the t test. Data collection through questionnaires wisth measurement using a scala likert 5 (five) alternative answers. On probability sampling technique with purposive sampling data collection method. The purposive sampling criteria is respondents who have visited and bought in Semarang Upnormal Warunk at least 2 (two) times and have income. The result of the study show that: Price perception has a postive and significant effect on customer satisfaction, product quality has a postive and significant effect on customer satisfaction, and service quality has a positive and significant effect on customer satisfaction. Keywords: Price Perception, Product Qualitu, Service quality and Customer Satisfaction